2004
DOI: 10.1161/01.cir.0000109493.05849.14
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Adrenomedullin Inhalation on Hemodynamics and Exercise Capacity in Patients With Idiopathic Pulmonary Arterial Hypertension

Abstract: Background-Adrenomedullin (AM) is a potent pulmonary vasodilator peptide. However, whether intratracheal delivery of aerosolized AM has beneficial effects in patients with idiopathic pulmonary arterial hypertension remains unknown. Accordingly, we investigated the effects of AM inhalation on pulmonary hemodynamics and exercise capacity in patients with idiopathic pulmonary arterial hypertension. Methods and Results-Acute hemodynamic responses to inhalation of aerosolized AM (10 g/kg body wt) were examined in 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(53 citation statements)
references
References 39 publications
2
50
0
1
Order By: Relevance
“…For this reason, AM has recently been given by inhalation in tests of its potential benefit in PH. With this method of administration, AM led to sustained and selective reduction of pulmonary artery pressure in a surfactant-depleted piglet model (145) and in rats with monocrotaline-induced PH (88) and improved pulmonary hemodynamics and exercise tolerance in patients with IPAH (87).…”
Section: )mentioning
confidence: 99%
“…For this reason, AM has recently been given by inhalation in tests of its potential benefit in PH. With this method of administration, AM led to sustained and selective reduction of pulmonary artery pressure in a surfactant-depleted piglet model (145) and in rats with monocrotaline-induced PH (88) and improved pulmonary hemodynamics and exercise tolerance in patients with IPAH (87).…”
Section: )mentioning
confidence: 99%
“…Furthermore, the same group reported that in patients with idiopathic pulmonary arterial hypertension, inhalation of AM lowered pulmonary artery pressure and resistance, improving exercise tolerance. 80 Although the long-term effects need to be examined, this novel approach seems promising for using AM in the treatment of primary pulmonary hypertension, for which few effective medical treatments are currently available.…”
Section: Vascular Protective Effects In Vivomentioning
confidence: 99%
“…Also it is a new tool for use in diagnosis of extracellular volume in renal insufficiency [63]. AM seems to have the potential to protect organs from damage, since AM supplementation was effective to improve hemodynamics in patients with congestive heart failure and hypertension [64][65][66][67].…”
Section: Ammentioning
confidence: 99%